Fiscal Responsiveness of Local Taxes: Elasticity and Tax Effort of Hotel and Restaurant Taxes to GRDP in Kabupaten Lombok Barat (2019–2023) - Siti Aulia Azmi; Douglas Chiguvi (Tinta Emas Publisher, 2025)
This study aims to analyze the level of elasticity of hotel and restaurant taxes to GRDP and analyze the tax effort in collecting hotel and restaurant taxes to GRDP of West Lombok Regency. By using a quantitative descriptive approach. The data analysis techniques in this study are elasticity analysis and tax effort analysis. The results of the study show that the level of elasticity of hotel taxes and restaurant taxes to GRDP of West Lombok Regency in 2019-2023 is included in the inelastic criteria, where the average value of hotel tax elasticity to GRDP is 0.53% and the average value of restaurant tax elasticity is 0.13%, so it can be said that the growth of Hotel Tax and restaurant tax is less sensitive to GRDP growth. Meanwhile, the analysis of tax effort or tax efforts in collecting Hotel Tax and Restaurant Tax to GRDP in West Lombok Regency over the past 5 years has a very low criterion. Where the average value of Hotel Tax Tax effort to GRDP is 0.15% and the average value of Restaurant Tax Tax effort is 0.14%. Therefore, it can be concluded that efforts to collect Hotel and Restaurant Tax in West Lombok Regency have not been running optimally. The West Lombok Regency Government is expected to improve tax collection by identifying and recording taxpayers who are not yet registered or who have the potential to pay taxes but have not yet paid according to regulations. This will also improve the tax object database.